Recycled asphalt mixtures produced with high percentage of different waste materials - Abreu, L. P. F. (2015)
The use of sustainable solutions in construction is not just an option, but is increasingly becoming a need of the Society. Thus, nowadays the recycling of waste materials is a growing technology that needs to be continuously improved, namely by researching new solutions for waste valorisation and by increasing the amount of wastes reused. In the paving industry, the reuse of reclaimed asphalt (RA) is becoming common practice, but needs further research work. Thus, this study aims to increase the incorporation of RA and other waste materials in the production of recycled asphalt mixtures in order to improve their mechanical, environmental and economic performance. Recycled mixtures with 50% RA were analysed in this study, including: i) RA selection, preparation and characterization; ii) incorporation of other waste materials as binder additives or modifiers, like used motor oil (UMO) and waste high density polyethylene (HDPE); iii) production of different mixtures (without additives; with UMO; with UMO and HDPE) and comparison of their performance in order to assess the main advantages of each solution. With this study it was concluded that up to 7.5 % of UMO and 4.0 % of HDPE can be used in a new modified binder for asphalt mixtures with 50 % of RA, which have excellent properties concerning the rutting with WTS = 0.02 mm/103 cycles, the fatigue resistance with Îµ6 = 160.4, and water sensitivity with an ITSR of 81.9 %.